Three isostructural hexanuclear lanthanide–organic frameworks for sensitive luminescence temperature sensing over a wide range. Issue 14 (21st March 2022) - Xia, Tifeng; Cao, Wenqian; Guan, Lingling; Zhang, Jun; Jiang, Fudong; Yu, Libing; Wan, Yating
Abstract : Three isostructural hexanuclear lanthanide–organic frameworks were constructed based on the cluster-based synthesis strategy for sensitive luminescence temperature sensing over a wide range. Abstract : Temperature sensing plays essential roles in both fundamental research and high-tech applications. In this work, three isomorphic hexanuclear lanthanide metal–organic frameworks (Ln-MOFs), Ln(BPDC- x N) (Ln = Eu 3+ /Tb 3+, x = 0, 1, 2) were prepared based on the cluster-based synthesis strategy with three structurally similar dicarboxylate ligands 4, 4′-biphenyldicarboxylic acid (H2 BPDC-0N), 6-(4-carboxyphenyl)nicotinic acid (H2 BPDC-1N), and [2, 2′-bipyridine]-5, 5′-dicarboxylic acid (H2 BPDC-2N) as the organic linkers. The as-synthesized Ln-MOFs were fully characterized using single-crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), elemental analysis (EA), and Fourier transform infrared spectra (FT-IR). Using a Eu 3+ /Tb 3+ co-doping approach, Eu0.001 Tb0.999 (BPDC- x N) ( x = 0, 1, 2) were identified as potential ratiometric luminescence thermometers. Since there are two suitable distances between the energy donors and acceptors within the framework for efficient energy transfer, all Eu0.001 Tb0.999 (BPDC- x N) ( x = 0, 1, 2) maintain high relative sensitivity over a wide temperature range from 50 K to 300 K.